Lithium ion battery diaphragm and preparation method thereof

By using the synergistic technology of porous sheet ceramics and glass fibers on the lithium-ion battery separator, the problems of insufficient thermal stability and low mechanical strength of the traditional separator in high temperature environments are solved, which significantly improves the thermal stability and mechanical strength of the separator and enhances the safety and performance of the battery.

CN119864593APending Publication Date: 2025-04-22HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510084799.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators lack thermal stability in high temperature environments and are prone to shrink or melt, resulting in short circuits and safety accidents inside the battery; their mechanical strength is also low and easy to break, affecting the reliability and performance of the battery.

Method used

Porous sheet ceramics and glass fibers are used to jointly improve the thermal stability and mechanical strength of the diaphragm. By forming a coating on the base film, the porous structure of the porous sheet ceramics and the fiber network structure of the glass fibers are used to enhance the thermal stability and mechanical strength of the diaphragm.

Benefits of technology

It significantly improves the thermal stability and mechanical strength of the diaphragm, prevents the diaphragm from shrinking or breaking caused by high temperature, reduces the risk of short circuits inside the battery, and improves the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005249794360000071
    Figure BDA0005249794360000071
  • Figure BDA0005249794360000072
    Figure BDA0005249794360000072
  • Figure BDA0005249794360000081
    Figure BDA0005249794360000081
Patent Text Reader

Abstract

The invention discloses a lithium ion battery diaphragm and a preparation method thereof, the lithium ion battery diaphragm comprises a base membrane and a coating on the base membrane, the coating comprises porous sheet ceramic and glass fiber, and the porous sheet ceramic is porous sheet alumina. The heat stability, the mechanical strength, the wettability and the ionic conductivity of the coating are enhanced through the synergistic effect of the glass fibers and the porous sheet-shaped ceramic, the glass fibers are inserted between pores of the porous sheet-shaped ceramic and gaps of the diaphragm, the effects of supporting and maintaining the stability of the pore structure are achieved, and the battery has long-term stable charging and discharging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium ion battery separator and a preparation method thereof. Background Art

[0002] With the rapid development of modern technology, the widespread use of electronic devices and the growing electric vehicle market, the demand for high-performance batteries is becoming increasingly urgent. Among the core components of batteries, the separator plays a vital role. It not only prevents short circuits caused by direct contact between positive and negative electrodes, but also affects the safety, performance and life of the battery.

[0003] Traditional battery separators have gradually revealed some shortcomings in the face of increasingly stringent usage requirements. For example, in high temperature environments, traditional separators have limited thermal stability and are prone to shrinkage or even melting, which can cause internal short circuits in the battery and lead to safety accidents. At the same time, their mechanical strength needs to be improved. During the assembly, transportation and use of the battery, they may be damaged by external forces, affecting the reliability of the battery.

[0004] In addition, in order to meet the requirements of high energy density and fast charge and discharge, the battery needs to have better ion transport performance and electrolyte affinity. The performance of traditional separators in this regard is often unsatisfactory, which limits the further improvement of battery performance.

[0005] In this context, developing a new type of battery separator has become a top priority. Summary of the invention

[0006] In view of the deficiencies of the prior art, an object of the present invention is to provide a lithium ion battery separator.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned lithium ion battery separator.

[0008] Another object of the present invention is to provide a slurry.

[0009] The purpose of the present invention is achieved through the following technical solutions.

[0010] A lithium-ion battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: porous flaky ceramics and glass fibers, wherein the ratio of the porous flaky ceramics to the glass fibers is (10-20):(15-45) by mass, and the porous flaky ceramics are porous flaky alumina.

[0011] In the above technical solution, the porous flaky ceramic is a long flaky structure, the pore diameter of the porous flaky ceramic is 30 to 150 nanometers, and the porosity of the porous flaky ceramic is 25 to 55%.

[0012] In the above technical solution, the length of the porous sheet-shaped ceramic is 0.8 to 3.5 microns, the width is 0.2 to 1.5 microns, and the thickness is 0.1 to 0.8 microns.

[0013] In the above technical solution, the diameter of the glass fiber is 20 to 120 nanometers, and the length of the glass fiber is 0.3 to 3.5 microns.

[0014] The preparation method of the above-mentioned lithium-ion battery separator includes: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining the lithium-ion battery separator, wherein the slurry includes: water, dispersant, porous sheet ceramics, glass fiber, binder and wetting agent.

[0015] In the above technical solution, the drying time is 1 to 3 minutes, and the drying temperature is 50 to 80°C.

[0016] In the above technical solution, the coating speed is 50-80 m / min.

[0017] In the above technical solution, the slurry is coated on one side or both sides of the base film.

[0018] A slurry comprises: water, dispersant, porous flaky ceramics, glass fiber, binder and wetting agent, wherein the ratio of water, dispersant, porous flaky ceramics, glass fiber, binder and wetting agent is (55-80): (0.1-0.8): (10-20): (15-45): (2-5): (0.05-1.0) by weight.

[0019] In the above technical solution, the binder is polyacrylate.

[0020] In the above technical solution, the wetting agent is sodium diisopropylnaphthalene sulfonate.

[0021] In the above technical solution, the dispersant is one or a mixture of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate and polyvinyl alcohol (PVA).

[0022] The method for preparing the slurry comprises: mixing water, a dispersant, porous sheet ceramics, glass fibers, a binder and a wetting agent until they are uniform to obtain the slurry.

[0023] In the above technical solution, the method for preparing the slurry specifically includes: mixing the porous sheet-like ceramic, glass fiber, water and dispersant until uniform to obtain a first solution, and mixing the first solution, a binder and a wetting agent until uniform to obtain a slurry.

[0024] In the above technical solution, porous sheet ceramics, glass fibers, water and dispersants are mixed and stirred at a rotation speed of 2500-3500 r / min and a revolution speed of 50-60 r / min for 30-40 minutes until uniform to obtain a first solution.

[0025] In the above technical solution, the first solution, the binder and the wetting agent are mixed, and stirred at a rotation speed of 200 to 300 r / min and a revolution speed of 30 to 40 r / min for 30 to 40 minutes until they are uniform to obtain a slurry.

[0026] Applications of porous ceramic sheets and glass fibers to synergistically improve the thermal stability, mechanical strength, wettability and / or ionic conductivity of separators.

[0027] Application of porous ceramic flakes and glass fibers to synergistically improve the bonding performance, liquid absorption rate and / or liquid retention rate of separators.

[0028] The application of porous sheet ceramics and glass fibers to synergistically improve battery charging and discharging efficiency.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. Improved thermal stability: The synergistic effect of glass fiber and porous flaky ceramics enhances the thermal stability of the coating, and jointly ensures the safe operation of the battery under high temperature conditions. When the internal temperature of the battery rises, the porous flaky ceramics and glass fibers can withstand higher temperatures without being easily deformed or melted, which can effectively prevent the diaphragm from undergoing severe thermal shrinkage or deformation due to high temperature, prevent the expansion of thermal runaway at high temperatures, reduce the risk of short circuit between the positive and negative electrodes, and improve the thermal safety performance of the battery. For example, in a high temperature environment, the diaphragm of the present invention can maintain good dimensional stability and avoid battery failure due to diaphragm shrinkage.

[0031] 2. Enhanced mechanical strength: Glass fibers are longer, and longer fibers can enhance the mechanical strength and stability of the fiber network, while porous flaky ceramics form a support structure similar to a skeleton, which can provide strong support for the diaphragm. The synergistic effect of glass fibers and porous flaky ceramics can enhance the overall mechanical strength of the diaphragm, making it more resistant to external impact, puncture, and various stresses that may be encountered during battery assembly and use, reducing the possibility of diaphragm damage, thereby improving the reliability and service life of the battery. For example, when subjected to external extrusion or puncture, the diaphragm of the present invention has better resistance and is not easily damaged.

[0032] 3. Improve electrolyte wettability: Porous flaky ceramics are porous structures with a large number of pores, which are interconnected to form a three-dimensional pore network structure. This structure increases the contact area between the electrolyte and the diaphragm, which is beneficial to the storage and transmission of the electrolyte, and can provide more channels and spaces for the migration of lithium ions, so that lithium ions can pass through the diaphragm more smoothly during the battery charging and discharging process, reduce the resistance of lithium ion transmission, and improve the electrochemical performance of the battery; porous flaky ceramics also have good electrolyte affinity, can better adsorb and retain electrolytes, and improve the wettability of electrolytes in the diaphragm; in the coating, glass fibers usually form a three-dimensional fiber network structure, and the fibers are intertwined and entangled with each other to form many pores and channels. Together with the stacking and arrangement of porous flaky ceramics, they provide the diaphragm with a higher porosity and air permeability, which can provide a good channel for the transmission of electrolytes, so that ions can pass through the diaphragm quickly, and thinner glass fibers can also increase the contact area with the electrolyte, which is beneficial to ion transmission. The surface of glass fiber also has a certain affinity for liquids. Although its main function is not to adsorb electrolytes, it can further improve the distribution and wetting effect of electrolytes in the coating after mixing with porous flaky ceramics. This good affinity for electrolytes helps to reduce the internal resistance of the battery, improve the battery's charge and discharge efficiency and cycle performance, and reduce local polarization caused by uneven distribution of electrolytes. The mixture of porous flaky ceramics and glass fibers can provide more pores and channels, which is conducive to the penetration and distribution of electrolytes in the diaphragm, improve the diaphragm's wettability and adsorption capacity for electrolytes, ensure smooth ion transmission inside the battery, and thus improve the battery's electrochemical performance and charge and discharge efficiency. The electrolyte can be more fully filled into the pores of the diaphragm, providing better conditions for the migration of lithium ions.

[0033] 4. Inhibit the growth of lithium dendrites: Lithium dendrites may pierce the diaphragm during the battery charging and discharging process, causing a short circuit inside the battery and causing safety problems. The diaphragm of the present invention has strong mechanical strength and a more uniform pore distribution, which can inhibit the formation and growth of lithium dendrites to a certain extent. The present invention reduces the damage of lithium dendrites to the diaphragm by improving the performance of the diaphragm, reduces the risk of short circuit, and improves the cycle performance and safety of the battery.

[0034] 5. Improve the electrolyte retention of the diaphragm: The synergistic effect of porous ceramic sheets and glass fibers can better preserve the electrolyte and reduce the loss of electrolyte, thereby ensuring that the battery always has enough electrolyte to participate in the reaction during long-term use, maintaining the stability of battery performance and extending the battery cycle life. Even after the battery is charged and discharged many times, the diaphragm can still maintain a good electrolyte retention.

[0035] 6. The porous flaky ceramic and the base film are well bonded through the adhesive, ensuring the stability of the coating on the base film and preventing the coating from falling off during battery use.

[0036] 7. Glass fibers are interspersed between the pores of the porous flaky ceramics and the gaps in the diaphragm. The addition of glass fibers does not block the pores of the ceramics. Instead, it fine-tunes the pore structure to a certain extent, plays a role in supporting and maintaining the stability of the pore structure, and prevents the pores from collapsing or deforming due to external forces or other factors during the use of the battery, thereby ensuring the long-term stability and effectiveness of the pore structure, and making the battery have long-term stable charge and discharge performance. Glass fibers are mixed with a binder (polymer) to form a polymer-glass fiber composite coating. This composite coating combines the advantages of the high porosity of glass fibers (porosity of about 60%) and the flexibility of polymers, further improving the comprehensive performance of the diaphragm. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0038] In the following embodiments, the electrolyte is a mixture of an electrolyte and a solvent, the electrolyte is lithium hexafluorophosphate (LiPF6), and the solvent is a mixture of propylene carbonate (PC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). The ratio of propylene carbonate (PC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) is 1:1:1 by mass, and the concentration of the electrolyte in the electrolyte is 1.2 mol / L.

[0039] In the following examples, the base film is a PE film with a thickness of 9 microns. The air permeability of the base film is 85 Sec / 100 ml, and the thermal diffusion coefficient is 0.0011 m 2 / s.

[0040] In the following examples, water is ultrapure water.

[0041] Thermomechanical analysis (TMA): The instrument used is TA400 produced by Shanghai Jituo Technology. The diaphragm is made into a sample with a width of 3 mm and a length of 8 mm and placed in TA400. The tensile force is set to 0.03N and the heating rate is set to 5℃ / min to obtain the membrane rupture temperature (used to characterize the mechanical strength).

[0042] Ionic conductivity: The test temperature is 23°C and the relative humidity is 55%.

[0043] Adhesion: Cut the 3M610 tape into strips of the width of the diaphragm, stick it flat on the coating surface of the diaphragm, roll it with a roller to ensure the fit, and use a tensile testing machine to peel off the 3M610 tape at a speed of 100 mm / min (peeling direction is 180°) to obtain the adhesion.

[0044] Examples 1 to 3

[0045] A method for preparing a slurry comprises: mixing porous flaky ceramics (porous flaky alumina), glass fibers, water and a dispersant, stirring the mixture at a rotation speed of 2500 r / min and a revolution speed of 50 r / min for 30 min until the mixture is uniform, to obtain a first solution; mixing the first solution, a binder and a wetting agent, stirring the mixture at a rotation speed of 250 r / min and a revolution speed of 30 r / min for 30 min until the mixture is uniform, to obtain a slurry, wherein the binder is polyacrylate (formed by polymerization of methyl acrylate, ethyl acrylate and butyl acrylate, purchased from Anhui Haofei New Materials Co., Ltd.), the wetting agent is sodium diisopropylnaphthalene sulfonate, and the dispersant is polyvinyl alcohol (PVA). The ratio of water, dispersant, porous flaky ceramics, glass fibers, binder and wetting agent is X by weight. The average pore diameter of the porous sheet ceramic (long sheet structure) is 85 nanometers, the porosity of the porous sheet ceramic is 30-45%, the length of the porous sheet ceramic is 0.8-2.0 micrometers, the width is 0.3-1.0 micrometers, and the thickness is 0.3-0.6 micrometers. The diameter of the glass fiber is 50 nanometers and the length is 1.5 micrometers. The value of X is shown in Table 1.

[0046] Table 1

[0047] Slurry X Example 1 64:0.8:10:25:3:0.2 Example 2 64:0.8:15:20:3:0.2 Example 3 64:0.8:20:15:3:0.2

[0048] Comparative Example 1

[0049] A method for preparing slurry is basically the same as Example 1, except that "porous flaky ceramic (porous flaky alumina)" is replaced by "conventional alumina (non-porous structure)". The particle size of the conventional alumina (particles) is D50: 1.5 microns.

[0050] Comparative Example 2

[0051] A method for preparing slurry is basically the same as that of Example 1, except that "porous flaky ceramic (porous flaky alumina)" is replaced by "boehmite". The particle size of the boehmite (particles) is D50: 1.6 microns.

[0052] Comparative Example 3

[0053] A method for preparing slurry is basically the same as Example 1, except that "porous flaky ceramic (porous flaky alumina)" is replaced by "barium sulfate". The particle size of the barium sulfate (particles) is D50: 1.0 micrometer.

[0054] Comparative Example 4

[0055] A method for preparing a slurry is basically the same as Example 1, except that "porous flaky ceramic (porous flaky alumina)" is replaced by "conventional alumina", and "glass fiber" is replaced by "mullite whisker". The particle size of conventional alumina (particles) is D50: 1.5 microns. Mullite whiskers: diameter is 200 to 400 nanometers, and length is 1 to 4 microns.

[0056] Comparative Example 5

[0057] A method for preparing a slurry is substantially the same as that of Example 1, except that "porous flaky ceramic (porous flaky alumina)" is replaced by "boehmite", and "glass fiber" is replaced by "mullite whisker". The particle size of the boehmite (particles) is D50: 1.6 microns. The mullite whisker has a diameter of 200 to 400 nanometers and a length of 1 to 4 microns.

[0058] Comparative Example 6

[0059] A method for preparing a slurry is substantially the same as that of Example 1, except that "porous flaky ceramic (porous flaky alumina)" is replaced by "barium sulfate" and "glass fiber" is replaced by "mullite whisker". The particle size of the barium sulfate (particles) is D50: 1.0 micrometer. The mullite whisker has a diameter of 200 to 400 nanometers and a length of 1 to 4 micrometers.

[0060] Examples 4 to 6 and Comparative Examples 7 to 12

[0061] A battery, comprising: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises a positive electrode current collector (aluminum foil) and a positive electrode coating loaded on the positive electrode current collector (the positive electrode material in the positive electrode coating is lithium cobalt oxide), and the negative electrode comprises a negative electrode current collector (copper foil) and a negative electrode coating loaded on the negative electrode current collector (the negative electrode material in the negative electrode coating is graphite), and the method for preparing the separator is: using a coating machine to coat the slurry on both sides of the base film, and pulling it into a drying device through a traction roller to dry it at 60° C. for 0.8 minutes to obtain the separator, wherein the coating speed is 80 m / min, the single-sided coating thickness formed by coating is 1.0 μm, and the total double-sided coating thickness is 2.0 μm. The slurry is one of the slurries prepared in Examples 1 to 3 and Comparative Examples 1 to 6.

[0062] Table 2

[0063]

[0064]

[0065] The battery separators prepared in the above examples and comparative examples were tested, and the test results are shown in Table 3.

[0066] Table 3

[0067]

[0068]

[0069] The batteries obtained in the above examples and comparative examples were tested at 2A / m 2 The battery was charged and discharged 500 times at the current density, and the test results are shown in Table 4. The batteries of Examples 4 to 6 still have a relatively high charge and discharge efficiency after 500 times of charge and discharge.

[0070] Table 4

[0071] Battery Charging capacity / mAh Discharge capacity / mAh Charge and discharge efficiency / % Example 4 2601.9 2588.5 99.5 Example 5 2620.1 2599.1 99.2 Example 6 2599.5 2582.2 99.3 Comparative Example 7 1996.2 1576.3 79.0 Comparative Example 8 1950.3 1450.2 74.4 Comparative Example 9 1805.6 1469.2 81.4 Comparative Example 10 1826.2 1522.5 83.4 Comparative Example 11 1899.2 1422.3 74.9 Comparative Example 12 1877.5 1510.5 80.5

[0072] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A lithium ion battery separator, characterized in that: include: The base film and the coating on the base film, the coating comprises: porous flaky ceramics and glass fibers, the ratio of the porous flaky ceramics to the glass fibers is (10-20): (15-45) by mass, and the porous flaky ceramics are porous flaky alumina.

2. The lithium-ion battery separator according to claim 1, characterized in that: The porous flaky ceramic is a long flaky structure, the pore diameter of the porous flaky ceramic is 30 to 150 nanometers, and the porosity of the porous flaky ceramic is 25 to 55%.

3. The lithium ion battery separator according to claim 1, characterized in that: The diameter of the glass fiber is 20 to 120 nanometers, and the length of the glass fiber is 0.3 to 3.5 microns.

4. The lithium-ion battery separator according to claim 1, characterized in that The porous sheet-shaped ceramic has a length of 0.8 to 3.5 microns, a width of 0.2 to 1.5 microns, and a thickness of 0.1 to 0.8 microns.

5. A method for preparing the lithium ion battery separator according to any one of claims 1 to 4, characterized in that: include: The slurry is coated on the base film and dried to obtain a coating on the base film to obtain a lithium ion battery separator. The slurry includes: water, dispersant, porous sheet ceramics, glass fiber, binder and wetting agent.

6. A slurry, characterized in that: include: Water, dispersant, porous flaky ceramics, glass fiber, binder and wetting agent, calculated by mass, the ratio of water, dispersant, porous flaky ceramics, glass fiber, binder and wetting agent is (55-80): (0.1-0.8): (10-20): (15-45): (2-5): (0.05-1.0).

7. The method for preparing the slurry according to claim 6, characterized in that: include: The water, the dispersant, the porous flake ceramic, the glass fiber, the binder and the wetting agent are mixed until uniform to obtain a slurry.

8. Application of porous ceramic sheets and glass fibers to synergistically improve the thermal stability, mechanical strength, wettability and / or ionic conductivity of the separator.

9. Application of porous ceramic sheets and glass fibers to synergistically improve the bonding performance, liquid absorption rate and / or liquid retention rate of diaphragms.

10. The application of porous sheet ceramics and glass fibers to synergistically improve battery charging and discharging efficiency.

Citation Information

Patent Citations

  • Battery separator, lithium ion battery and preparation method of lithium ion battery

    CN108598342A

  • Separator with a ceramic-comprising separator layer

    CN112042005A

  • separator

    US20130157109A1